Understanding the diffusion of AI-generative (ChatGPT) in higher education: Does students' integrity matter? - Mohamed Bouteraa; Saeed Awadh Bin-Nashwan; Meshari Al-Daihani; Khadar Ahmed Dirie; Abderrahim Benlahcene; Mouad Sadallah; Hafizah Omar Zaki; Suddin Lada; Rudy Ansar; Lim Ming Fook; Brahim Chekima (Elsevier, 2024)
ChatGPT, an AI-powered language model, is revolutionising the academic world. Scholars, researchers, and students use its advanced capabilities to achieve their educational objectives, including generating innovative ideas, delivering assignments, and conducting extensive research projects. Nevertheless, the use of ChatGPT among students is contentious, giving rise to significant apprehensions regarding integrity and AI-facilitated deceit. At the same time, scholarly communities currently need more well-defined standards for adopting such academia-oriented technology. This study aims to determine students’ use of ChatGPT using the Unified Theory of Acceptance and Use of Technology (UTAUT) and Social Cognitive Theory (SCT), notably the role of students’ integrity in determining adoption behaviour. The analysis of 921 responses demonstrated that the utilisation of ChatGPT is influenced positively by performance expectancy, social influence, educational self-efficacy, tech nology self-efficacy, and personal anxiety. Conversely, student integrity was found to negatively impact usage. Remarkably, student integrity has a positive moderating effect between effort expectancy and ChatGPT usage. At the same time, it has a negative moderating effect on the link between performance expectancy and technology self-efficacy with ChatGPT usage. Hence, we propose that the academic community, AI language model de velopers, publishers, and relevant stakeholders collaborate to establish explicit rules for the utilisation of AI chatbots in an ethical manner for educational purposes.